Effects of xanthan gum on the rheological properties of soy protein dispersion - Bi, Chonghao; Gao, Fei; Zhu, Yingdan; Ji, Fang; Zhang, Yulai; Li, Dong; Huang, Zhigang (International Journal of Agricultural and Biological Engineering, 2018)
This study focused on the effects of addition of xanthan gum (XG) on the rheological properties of soy protein isolate (SPI) solution. Three types of tests (steady shear test, strain sweep test, and frequency sweep test) were performed to figure out the influences of shear rate on the viscosity of the SPI-XG hybrid system, the effects of strain variable on the storage modulus of the hybrid system, and the effects of frequency on both the storage modulus and the loss modulus of the hybrid system, respectively. SPI-XG hybrid system showed more obvious shear-thinning properties compared to pure SPI and pure XG solution. Meanwhile, it was found that the critical point of hybrid system was highly related to the XG concentration. XG can postpone the critical point strain amplitude to a higher value, and the addition of XG can enhance the strain resistance of hybrid system. The concentration of XG influenced the viscoelastic frequency dependence of the hybrid system significantly and complicatedly. After the addition of XG, the correlation between G′ and frequency changed from negative to positive. Keywords: rheological property, soy protein isolate (SPI), xanthan gum (XG), temperature, frequency independence DOI: 10.25165/j.ijabe.20181102.3253 Citation: Bi C H, Gao F, Zhu Y D, Ji F, Zhang Y L, Li D, et al. Effects of xanthan gum on the rheological properties of soy protein dispersion. Int J Agric & Biol Eng, 2018; 11(2): 208–213.